1993
DOI: 10.1111/j.1749-6632.1993.tb55559.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxytocin on Renal Hemodynamics and Sodium Excretiona

Abstract: Acute administration of physiological doses of synthetic OT to conscious Long-Evans and Brattleboro homozygous diabetes insipidus rats produced a modest increase in GFR and effective filtration fraction. Chronic administration of OT to DI rats for 9 days in dosages that were antidiuretic (plasma OT ca. 100 pg/ml) increased both GFR and ERPF by 40%. Table 1 summarizes these renal hemodynamic changes and compares them to the renal effects of VP. Further investigation is needed to define the mechanisms responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 20 publications
2
58
0
2
Order By: Relevance
“…The acute renal actions of OT include increased GFR, filtration fraction and sodium excretion without affecting potassium excretion (17) in Brattleboro rats with a hereditary lack of AVP (18), which suggests that OT exerts renal actions independent of vasopressin. Oxytocin also has tubular actions (19) on apical sodium conductance that may be related to increases in intracellular [Ca 2+ ] and cAMP production (20).…”
Section: Natriuretic Action Of Oxytocinmentioning
confidence: 99%
“…The acute renal actions of OT include increased GFR, filtration fraction and sodium excretion without affecting potassium excretion (17) in Brattleboro rats with a hereditary lack of AVP (18), which suggests that OT exerts renal actions independent of vasopressin. Oxytocin also has tubular actions (19) on apical sodium conductance that may be related to increases in intracellular [Ca 2+ ] and cAMP production (20).…”
Section: Natriuretic Action Of Oxytocinmentioning
confidence: 99%
“…In the rat, these hormones promote water reabsorption (McDonald, Miller, Anderson, Berl & Schrier, 1976) and sodium excretion (Conrad, Gellai, North & Valtin, 1993) by the kidney. Both hormones, therefore, have been proposed to participate in the regulation of body fluid balance.…”
mentioning
confidence: 99%
“…The present studies suggest that the altered responsiveness does not result from changes in GFR, but observations were performed on a limited number of animals. It has, however, been reported that in the male rat doses of oxytocin which do not affect GRF are nevertheless natriuretic (Conrad et al 1986;Forsling et al 1994). Oxytocin binding sites have been identified in the inner medullary collecting duct (Stoeckel et al 1987) and evidence has been provided for an inhibitory effect of oxytocin on sodium transport across the luminal membrane of rabbit cortical collecting duct segments perfused in vitro (Inoue et al 1993).…”
Section: Discussionmentioning
confidence: 99%